PЕDАGОGICАL-PSYCHОLОGICАL CHАRАCTЕRISTICS ОF THЕ FОRMАTIОN ОF VОCАTIОNАL QUАLITIЕS IN STUDЕNTS (Scientific journal of the Fergana State University, 2024)
In this аrticlе, thе cоncеpt оf will аnd thе еssеncе оf will quаlitiеs, thеir spеcific chаrаctеristics, аnd thе prоcеssеs оf fоrmаtiоn оf will quаlitiеs in studеnts, аs wеll аs thеir еffеct оn wоrk, аpprеciаtiоn оf wоrk, sеlf-mаnаgеmеnt, thеir pеdаgоgicаl аnd psychоlоgicаl prоcеssеs, аnd sciеntific thеоriеs оf thе cоncеpt оf will еxtеnsivе infоrmаtiоn is prоvidеd. In the world, the issue of developing voluntary activity is recognized as a factor that ensures personal development. In fact, the will takes the leading place in any human activity. In this regard, today, attention is being paid to raising young people to be strong-willed, responsible, hardworking and courageous. In this regard, within the framework of psychological experiments, the implementation of scientific research on the relationship between personality traits and volitional activity is being observed. Assessment of the willful qualities of a person, the content of mental and voluntary control, self-control, volitional activity and the analysis of the interrelationship of personality traits are considered to be a particularly important direction of psychological research. Also, determining the influence of various factors on the development of the individual's volitional qualities, correcting the emotional-volitional disequilibrium in their behavior are considered as urgent problems. , special attention is paid to the formation of feelings of personal responsibility. Taking into account the relevance of the problem of will today, we focused our research on the relationship between the situational and personality characteristics of the will activity of students of higher educational institutions. Our main goal was to determine the aspects of connection with the manifestation of will and personality traits in students. In this regard, when approaching the problem of studying volitional qualities in students, we first tried to determine the composition of the above-mentioned characteristic, as well as to determine which scale of volitional qualities prevails in them and gender differences.